Droplets Self-Draining on the Horizontal Slippery Surface for Real-Time Anti-/De-Icing - Han, Xiao; Sun, Xu; Zhao, Di; Sun, Mingjia; Liu, Kesong; Heng, Liping; Jiang, Lei (Nano-Micro Letters, 2025)
Undesired ice accumulation on infrastructure and transportation systems leads to catastrophic events and significant economic losses. Although various anti-icing surfaces with photothermal effects can initially prevent icing, any thawy droplets remaining on the horizontal surface can quickly re-freezing once the light diminishes. To address these challenges, we have developed a self-draining slippery surface (SDSS) that enables the thawy droplets to self-remove on the horizontal surface, thereby facilitating real-time anti-icing with the aid of sunlight (100 mW cm−2). This is achieved by sandwiching a thin pyroelectric layer between slippery surface and photothermal film. Due to the synergy between the photothermal and pyroelectric layers, the SDSS not only maintains a high surface temperature of 19.8 ± 2.2 °C at the low temperature ( −20.0 ± 1.0 °C), but also generates amount of charge through thermoelectric coupling. Thus, as cold droplets dropped on the SDSS, electrostatic force pushes the droplets off the charged surface because of the charge transfer mechanism. Even if the surface freezes overnight, the ice can melt and drain off the SDSS within 10 min of exposure to sunlight at −20.0 ± 1.0 °C, leaving a clean surface. This work provides a new perspective on the anti-icing system in the real-world environments. Highlights: 1 Self-draining slippery surface with light-thermal-electric synergy were fabricated to auto anti/de-icing even on horizontal devices. 2 The synergy of photothermal conversion and thermoelectric coupling enables the ice melting, and self-draining of thawy droplets at the same time, avoiding the risk of re-freezing. 3 The processes of no matter in ice melting or droplets repulsion on horizontal surface need no additional energy input, just with assistance of sunlight.